Dual-Wavelengths Spectrophotometry for Improving the Determination of Acetone in Waste Water - Gao, Hong-Wen (Asian Journal of Chemistry, 2010)
The conventional reaction of acetone with furfural in the presence of sulfuric acid to form a red substance which has been applied for the improvement of the determination of trace amounts of acetone in water in waste water by the updated method named primary-secondary wavelengths spectrophotometry (PSWS). The results showed that the analytical precision and accuracy were increased and gave the higher sensitivity than the ordinary spectrophotometry. The relative standard deviations were less than 2% and the recovery rate of acetone between 92.7 and 101%.